COMBINATION OF TRANSFORMATIONAL AND COMMUNITY-BASED LEADERSHIP MODEL IN THE DEVELOPMENT OF PUJON KIDUL TOURISM VILLAGE, INDONESIA - Cecep Ucu Rakhman; Lutfiandina Kharisma; Mohamad Liga Suryadana (Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: Leadership is part of the success of village development. Leaders can choose and apply a leadership model that suits their organization. Background Problems: This research was conducted to analyze the applied leadership model in village tourism. The Head of Pujon Kidul Tourism Village is one of the figures who has succeeded in leading his village and bringing positive changes to the community. Novelty: This study focuses on the leadership model of the village head in managing a tourism village. Research Methods: Data collection was carried out by observation, interviews, and documentation. Interviews were conducted using an interview guide instrument containing 12 questions divided into three dimensions (leadership, tourism, and successful factor in leadership). This qualitative research using a case study as a research design.Finding/Results: The application of a combination of transformational and community-based leadership styles in the tourism village of Pujon Kidul has succeeded in improving Pujon Kidul Tourism Village. Usually, the leader only uses transformational leadership in general, but in this village, the leader uses a combination of transformational and community-based leadership. Conclusion: The leadership model used by the head of the Pujon Kidul tourism village is a combination of transformational and community-based leadership community-based leadership.